Banking liquidity and the possibility of invested it in enhancing the solvency For a number of commercial banks in Iraq - عبد الحميد مناهل مصطفى; كاظم حسن عبد نزال (Journal of Economics and Administrative Sciences, 2020)
The primary function of commercial banks is the process of converting liquid liabilities such as deposits to illiquid assets, (also known as a loan), liquid assets, (aka cash and cash equivalent) in a balanced manner between liquid and illiquid assets, that guaranteed the preservation of the rights of depositors and the bank and not by converting liquid liabilities into liquid assets in a very large percentage. This comes from its role as depository and intermediary institutions between supply and demand, therefore, we find that the high indicators of bank liquidity and solvency may reflect a misleading picture of the status of commercial banks, to some extent in terms of the strength of their balance sheets and their adherence to the instructions and standards of the Central Bank. Are these indicators result from optimal policies of these banks, are they confused policies, or are they as a result of the situation of the prevailing local economy? Thus, the bank’s liquidity is deemed as the backbone of the bank’s work, in fact, bank’s work depends on it, since it Reflected the status of solvency, sustainability, and continuity, Consequently, this importance led us to choose the subject of the study. For the purpose of identifying this problem and try to find solutions for it, this study aimed to identify the possibility of investing banking liquidity in order to enhance the solvency of commercial banks. This study was conducted on a sample of Iraqi commercial banks, included three banks, of which two private banks and a government bank, and for the period from 2011 to 2017, in order to identify the nature of investment and credit policies of these banks and analyze their strengths and weaknesses, as well as their roles in enhancing their solvency. The study relies on the combination of inductive and deductive approaches. In addition, the study depends on the descriptive-analytical approach in analyzing the taken data and information of the governmental and private banks from the official bodies, Central Bank of Iraq, and the Iraqi Stock Exchange. At the end of the study, the researcher has reached a number of conclusions, and this includes that the public and privet commercial banks suffer from limited credit and investment activity, which caused high liquidity and liquid assets at the expense of other assets at banks, Naturally, this means the accumulation of non-income liquid funds which significant have an impact on its solvency, and formed "phantom financial solvency", This result reflects the fear of these banks to Employ their liquidity in fields of investment and credit, Involves some type of risk.